G+(-7)=12

Simple and best practice solution for G+(-7)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for G+(-7)=12 equation:


Simplifying
G + (-7) = 12
G + -7 = 12

Reorder the terms:
-7 + G = 12

Solving
-7 + G = 12

Solving for variable 'G'.

Move all terms containing G to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + G = 12 + 7

Combine like terms: -7 + 7 = 0
0 + G = 12 + 7
G = 12 + 7

Combine like terms: 12 + 7 = 19
G = 19

Simplifying
G = 19

See similar equations:

| 50/2=3x-2 | | -48+-12+x=-28 | | 3y=17+7 | | 5h-3=7 | | 6xsquared=36 | | 4x^2+25=9x^2 | | -26x-36=30 | | P=4(4.6+1.25) | | 4x^2+25=9z^2 | | 3x^1y^3*4y^3= | | 5-g/4=3 | | 5(1+104x)=8 | | 2x+15+6x-10=180 | | -3/8v=18 | | 4x^3y^3*4x^4y^4= | | 10x+20x-6+5=-2x+5-6 | | v/17.5=7 | | x^2+9x+25=2x+1 | | 7m-5=51 | | 9x+12y=320 | | 73/331 | | 2x+3y+6z=24 | | y=mx+5 | | (6u-7v)(6u+7v)= | | 8x-3=3-2(4x-3) | | 6y-10-3y+6=0 | | 9+4q=11+3q | | (-3u/v^3)^2 | | (2-a)(5z-7)=0 | | x/3-4=x-7 | | -4a+2=4a+82 | | e/-6=4 |

Equations solver categories